If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5(x + -4) = -2 + 4x + -20 Reorder the terms: 3x + -5(-4 + x) = -2 + 4x + -20 3x + (-4 * -5 + x * -5) = -2 + 4x + -20 3x + (20 + -5x) = -2 + 4x + -20 Reorder the terms: 20 + 3x + -5x = -2 + 4x + -20 Combine like terms: 3x + -5x = -2x 20 + -2x = -2 + 4x + -20 Reorder the terms: 20 + -2x = -2 + -20 + 4x Combine like terms: -2 + -20 = -22 20 + -2x = -22 + 4x Solving 20 + -2x = -22 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 20 + -2x + -4x = -22 + 4x + -4x Combine like terms: -2x + -4x = -6x 20 + -6x = -22 + 4x + -4x Combine like terms: 4x + -4x = 0 20 + -6x = -22 + 0 20 + -6x = -22 Add '-20' to each side of the equation. 20 + -20 + -6x = -22 + -20 Combine like terms: 20 + -20 = 0 0 + -6x = -22 + -20 -6x = -22 + -20 Combine like terms: -22 + -20 = -42 -6x = -42 Divide each side by '-6'. x = 7 Simplifying x = 7
| 3y-17=40 | | 5+x=7-8x | | -8y+12=52 | | 2-7(3x-2)=30 | | 9x+5=9x-6 | | 74=3u+4 | | .25z=10 | | 3x-5(x-4)=-2+4-20 | | 2.5r=85 | | 3x-6((12-5x)3)=15 | | (2a+4)(a+6)= | | 0.6t=72 | | 6.6a+15=81 | | h(x)=x^3-x^2-6x | | 81^(5/2) | | y=5x+273 | | 5x-2(x-5)=-8+5x+12 | | 5=2y-15 | | 0.00016-0.0004x=x^2 | | 91x-y-2z+x+5y+2z= | | 2(x^2-10x^2-24)=-80 | | 4x+7-9=14 | | 2y=8+x | | X-0.10x=1738.22 | | 16x-(-10)=-38 | | ln(4x+1)+ln(4x-7)-ln(9)=0 | | x-4+y=120 | | 28-4d=3x | | 2v-66=v-14 | | 20+8x=60 | | 8x+8=-17+3x | | 15=-5/6(10)-2 |